Influence of pregnancy and early lactation on the serum levels of iron, copper and, zinc in crossbred heifers* - JACOB, SHIBU K; PHILOMINA, P T; RAMNATH, V (The Indian Journal of Animal Sciences, 2014)
The serum concentration of iron, copper arid zinc were evaluated in healthy crossbred heifers of Kerala and after conception. at different stages of pregnancy and early lactation, There was an increase in the serum concentration of iron till mid gestation (5 months prcgnancy,1.68±0.14ppm) and value was lowered as pregnancy advanced 19 months pregnancy. 1.23±0.07ppm) and during early lactation (first month of lactalion. 1.13±0.09 ppm). There was a high fluctuation in the serum copper level during differem stages of gestation with a signincant increase during the advanced month (ninth month pregnancy. 0,81±0.04ppm) of pregnancy as well as in the first month of lactation (0.89±0.07ppm). The serum zinc level declined from the fourth month of pregnancy (0.76±0.04ppm) up to eighth month and thereafter, increased during the ninth month of pregancy (0.87±0.04ppm) and first month of lactation.